Lymphocytic Esophagitis With Predominance of CD4 T Cells and Expansion of Th1 Cells Is Associated With Achalasia. Issue 2 (20th February 2021) - Muller, Kristen; Xiao, Jenny; Putra, Juan; Rothstein, Richard; McCourt, Collin; Konnikova, Liza; Lisovsky, Mikhail
Abstract: Objectives: Although histologic features in biopsies suggesting a possibility of achalasia would be helpful diagnostically, such features remain unknown. The goal of this study was to explore the prevalence, histologic features, and immunophenotype of lymphocytic esophagitis (LyE) in achalasia biopsies. Methods: The study group consisted of 57 patients with achalasia. Controls comprised 52 patients with severe gastroesophageal reflux disease (GERD) and normal esophageal motility. CD4/CD8 immunophenotype of lymphocytes was analyzed by immunohistochemistry Results: LyE was identified in 30% (17/57) of patients with achalasia and 6% (3/52) of patients with GERD, indicating a strong association with achalasia (odds ratio, 6.94; 95% confidence interval, 1.90-25.38). LyE was focal in 59% (10/17) of the cases and diffuse in 41% (7/17). CD4 T-cell predominance over CD8 T cells was observed in 88% of patients with achalasia and LyE. T helper 1 (Th1) cells, but not T helper 2 cells, were expanded in CD4 T cells; in the absence of evident infection, this was compatible with the role of Th1 cells in organ-specific autoimmunity. Conclusions: Achalasia should be considered in the differential diagnosis of clinical entities associated with CD4-predominant LyE. Additional studies to explore the significance of Th1 cells in achalasia-associated LyE are warranted.